2008
DOI: 10.1038/onc.2008.153
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of matrix metalloproteinase 1 in dermal fibroblasts from DNA repair-deficient/cancer-prone xeroderma pigmentosum group C patients

Abstract: Xeroderma pigmentosum (XP) is a rare, recessively inherited genetic disease characterized by skin cancer proneness and premature aging in photoexposed area. The disease results from defective nucleotide excision repair of ultraviolet (UV)-induced DNA lesions. Reconstruction of group C (XP-C) skin in vitro previously suggested that patients' dermal fibroblasts might be involved in promoting skin cancer development, as they elicited microinvasions of both control and XP-C keratinocytes within dermal equivalents.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 52 publications
1
20
0
Order By: Relevance
“…Increased MMP1 levels were shown in dermal fibroblasts, dermal equivalents, and skin sections from XP patients mutated in the XPC gene, leading to the suggestion that MMP-1 overespression could be a worsening actor toward exacerbated premature skin aging and tumor susceptibility in these patients. Nevertheless, no evidence of ECM alterations was reported in the analyzed XP-C cells and tissues (39). Further studies are needed to ascertain whether the reduced levels of COL1 observed in the present study together with the previously reported lowered amount of COL6A1 secreted by TTD dermal fibroblasts (6) might create a microenvironment not conducive for cancer cells to survive and grow.…”
Section: Discussionmentioning
confidence: 52%
“…Increased MMP1 levels were shown in dermal fibroblasts, dermal equivalents, and skin sections from XP patients mutated in the XPC gene, leading to the suggestion that MMP-1 overespression could be a worsening actor toward exacerbated premature skin aging and tumor susceptibility in these patients. Nevertheless, no evidence of ECM alterations was reported in the analyzed XP-C cells and tissues (39). Further studies are needed to ascertain whether the reduced levels of COL1 observed in the present study together with the previously reported lowered amount of COL6A1 secreted by TTD dermal fibroblasts (6) might create a microenvironment not conducive for cancer cells to survive and grow.…”
Section: Discussionmentioning
confidence: 52%
“…The mechanism by which persistent DSBs induces an oxidative stress is not known but may be related to an elevated cellular metabolism to achieve DNA repair. In agreement with this hypothesis, the existence of a link between defects in DNA damage repair pathways and increased ROS production is now becoming more and more clear [21]–[24]. Whatever the mechanism, the presence of persistent DSBs in the absence of p400 may contribute to the observed increase in ROS levels.…”
Section: Discussionmentioning
confidence: 85%
“…Strikingly more and more evidence suggests that persistent DNA damage (due for example to defective DNA repair pathways) induces an oxidative stress [21]–[24]. Since p400 depleted cells present an increase in DNA breaks (see Figure 2D and 2E), we tested whether this increase in DNA damage could participate in ROS production.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly over-expression of these MMPs has been reported in CAF of sporadic BCCs [47], [48]. MMP1 over-expression was also observed in dermal fibroblasts from xeroderma pigmentosum group C patients and is thought to be involved in skin cancer development in these patients [49]. Epidermal over-expression of MMP1 in transgenic mice induces epidermal hyperplasia [50].…”
Section: Discussionmentioning
confidence: 98%